Cell cycle and radiosensitivity of progeny of irradiated primary cultured human hepatocarcinoma cells - Liu, Zhi-Zhong (World J Gastroenterol, 2005)
AIM: To evaluate the change of growth characteristics and radiosensitivity of irradiated primary cultured human hepatocarcinoma cells. METHODS: All tumor tissue samples were obtained from 39 hepatocarcinoma patients with a mean age of 49.6 years (range 22-76 years). We divided the samples into irradiated group and non-irradiated group and measured their plating efficiency (PE), population doubling time (PDT), radiosensitivity index SF2 and cell cycle. RESULTS: The PDT of primary culture of hepatocarcinoma cells was 91.0±6.6 h, PE was 12.0±1.4%, SF2 was 0.41±0.05%. The PDT of their irradiated progeny was 124.8±5.8 h, PE was 5.0±0.7%, SF2 was 0.65±0.09%. The primary cultured human hepatocarcinoma cells showed significant S reduction and G(2) arrest in a dose-dependent manner. The progeny of irradiated primary cultured hepatocarcinoma cells grew more slowly and its radiosensitivity increased. CONCLUSION: The progeny of irradiated primary cultured human hepatocarcinoma cells grows more slowly and its radiosensitivity increases.